The Psychological Characteristics of Stinginess Among University Students - Nuraddinovna, Davletova Nodira (Jurnal Psikologi, 2025)
This study aims to analyze the fairness of royalty agreements between songwriters and singers in the Indonesian music industry and to assess the extent to which legal protection of songwriters' economic rights has been implemented. The research employs a normative juridical approach with qualitative analysis. Data were obtained through literature review, including statutory regulations, John Rawls’ theory of distributive justice, and contract law theory, as well as case studies of existing royalty agreement practices in Indonesia's music industry. The findings reveal that songwriters often hold a weaker bargaining position compared to singers or producers during royalty contract negotiations, resulting in disproportionate revenue sharing. Although Law No. 28 of 2014 on Copyright normatively protects creators' economic rights, its implementation remains ineffective. Collective Management Organizations (LMK) have also not optimally represented songwriters’ interests due to institutional limitations and the absence of fair contract standards. The study recommends strengthening regulations, developing fair royalty agreement templates, and enhancing the role of LMK in order to build a more equitable contractual system that supports an inclusive and sustainable music ecosystem.